A STUDY ON STUDENTS’ DIFFICULTIES IN LEARNING VOCABULARY - Rohmatillah, Rohmatillah (English Education: Jurnal Tadris Bahasa Inggris, 2014)
The objectives of the research entitled “A Study on Students’ Difficulties in Learning Vocabulary” were to find out kinds and factors of students’ difficulties in learning vocabulary.  The subject of this study was the students of the first semester of English Education Department at IAIN who took vocabulary class. This study employed a qualitative research design, implementing characteristics of a case study. For gaining the data, the researcher used interview and questionnaire. All the data were analyzed descriptively. The findings showed that the students still faced the problems or difficulties in vocabulary learning. Kinds of difficulties faced by students in vocabulary learning were various. Kinds of difficulties faced by the students were (1) almost all of the students have difficulties in pronouncing the words, (2) how to write and spell, (3) the different grammatical form of a word known as inflections was one of causes of students difficulties in learning vocabulary. In addition, (4) the students found difficulties in choosing the appropriate meaning of the words and (5) also still confuse in using the word based on the context. The last, (6) the students were also still confuse when they found words or expression that were idiomatic. There were some factors that caused students’ difficulties in learning vocabulary (1) the written form is different from the spoken form in English, (2) The number of words that students need to learn is exceedingly large, (3) the limitations of sources of information about words, (4) The complexity of word knowledge. Knowing a words involves much more than knowing its dictionary definition, (5) causes of lack of understanding of grammatical of the words, (6) the incorrect pronunciation is often caused by the lack of sound similarity between English and the students’ native language.